Large Multicohort Study Reveals a Prostate Cancer Susceptibility Allele at 5p15 Regulating TERT via Androgen Signaling-Orchestrated Chromatin Binding of E2F1 and MYC - Dong, Xiaoming; Zhang, Qin; Hao, Jinglan; Xie, Qianwen; Xu, Binbing; Zhang, Peng; Lu, Haicheng; Huang, Qilai; Yang, Tielin; Wei, Gong-Hong; Na, Rong; Gao, Ping (Frontiers in Oncology, 2021)
Aberrant telomerase reverse transcriptase (TERT) expression is crucial for tumour survival and cancer cells escaping apoptosis. Multiple TERT-locus variants at 5p15 have been discovered in association with cancer risk, yet the underlying mechanisms and clinical impacts remain unclear. Here our association studies showed that the TERT promoter variant rs2853669 confers a risk of prostate cancer (PCa) in different ethnic groups. Further functional investigation revealed that the allele-specific binding of MYC and E2F1 at TERT promoter variant rs2853669 associate with elevated level of TERT in PCa. Mechanistically, androgen stimulations promoted the binding of MYC to allele T of rs2853669 thereby activating TERT, whereas hormone deprivations enhanced E2F1 binding at allele C of rs2853669, thus upregulate TERT expression. Notably, E2F1 could cooperate with AR signaling to regulate MYC expression. Clinical data demonstrated synergistic effects of MYC/E2F1/TERT expression or with TT and CC genotype of rs2853669 on PCa prognosis and severity. Strikingly, single-nucleotide editing assays showed that CC genotype of rs2853669 obviously promotes epithelial-mesenchymal transition (EMT) and the development of castration-resistant PCa (CRPC), confirmed by unbiased global transcriptome profiling. Our findings thus provided compelling evidence for understanding the roles of noncoding variations coordinated with androgen signaling and oncogenic transcription factors in mis-regulating TERT expression and driving PCa.